Synthesis of a UCNPs@SiO2@gadofullerene nanocomposite and its application in UCL/MR bimodal imaging. Issue 101 (17th October 2016) - Li, Cheng; Cui, Rongli; Feng, Liangzhu; Li, Juan; Huang, Huan; Yao, Huanli; Guo, Xihong; Dong, Jinquan; Xing, Gengmei; Liu, Zhuang; Sun, Baoyun
Abstract : A novel bimodal imaging agent (GdF–UCNPs) has been designed through conjugating the water-soluble polyhydroxy Gd@C82 -PCBM with silica coated UCNPs. Abstract : Multimodal imaging provides more complementary information than single mode imaging. Herein, we have developed a novel bimodal imaging agent (GdF–UCNPs) through conjugating paramagnetic water-soluble polyhydroxy Gd@C82 -PCBM with silica coated NaYF4 :Yb, Er nanoparticles. In the new contrast agent, the stable silica shell and the carbon cage structure protect the encaged inner rare earth ions, which results in low toxicity. The resulting nanoconjugates exhibit strong luminescence and present efficient MRI contrast ( r 1 = 11.89 mM −1 s −1 ). Ex vivo and in vivo bimodal imagings were carried out in a mouse model. The results prove that the nanocomposites are useful as bimodal imaging agents for luminescence/MR imaging in biomedical research.